2019
DOI: 10.1128/aem.02095-19
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid and Sugar Catabolism in the Marine Bacterium Phaeobacter inhibens DSM 17395 from an Energetic Viewpoint

Abstract: Growth energetics and metabolic efficiency contribute to the lifestyle and habitat imprint of microorganisms. Roseobacters constitute one of the most abundant and successful marine bacterioplankton groups. Here, we reflect on the energetics and metabolic efficiency of Phaeobacter inhibens DSM 17395, a versatile heterotrophic roseobacter. Fourteen different substrates (five sugars and nine amino acids) and their degradation pathways were assessed for energetic efficiencies based on catabolic ATP yields, calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 71 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…Finally, the conspicuous enrichment of the exoproteome of the Δ262 mutant with a multitude of diverse proteins may hint at a profound difference in the membrane/cell envelope permeability between the wild type and the Δ262 mutant. While the wild type is the model system prima facie for system biology experiments with P. inhibens DSM 17395, several lines of evidence qualify the Δ262 mutant as a potentially more suitable alternative: (i) the observed overall metabolic congruence (except for transportome) between both genotypes, (ii) the recently reported influence of growth substrates on TDA formation in the wild type [Wünsch et al, 2019], (iii) the markedly better growth performance of the Δ262 mutant, and (iv) the avoidance of the multiple adverse effects of TDA with the Δ262 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the conspicuous enrichment of the exoproteome of the Δ262 mutant with a multitude of diverse proteins may hint at a profound difference in the membrane/cell envelope permeability between the wild type and the Δ262 mutant. While the wild type is the model system prima facie for system biology experiments with P. inhibens DSM 17395, several lines of evidence qualify the Δ262 mutant as a potentially more suitable alternative: (i) the observed overall metabolic congruence (except for transportome) between both genotypes, (ii) the recently reported influence of growth substrates on TDA formation in the wild type [Wünsch et al, 2019], (iii) the markedly better growth performance of the Δ262 mutant, and (iv) the avoidance of the multiple adverse effects of TDA with the Δ262 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Phe, the rapid remineralization of Ala-N to ammonium was likely due to the utilization of Ala-C. Pyruvate, an important precursor of citric acid cycle, is the direct product of Ala transamination (Drüppel et al, 2014). Thus, Ala may have been rapidly deaminated or transferred to pyruvate to fuel the growth of the microbial community (Drüppel et al, 2014;Wünsch et al, 2019). The higher yield of uncharacterizable DON from AVFA than single amino acids combined (Figure S3 in Supporting Information S1) suggests that peptide structure may have also played a role in the decomposition process.…”
Section: The Fates Of 15 N Depend On Specific Amino Acidsmentioning
confidence: 99%
“…This apparent decoupling suggested that the metabolic pathways of C and N differed. The C from labile organic substrate is likely used as energy source to fuel the growth of microbial community (e.g., Drüppel et al, 2014;Wünsch et al, 2019), and thus quickly remineralized into CO 2 (e.g., Lønborg et al, 2009;Ogawa et al, 2001).…”
Section: The Fates Of 15 N Depend On Specific Amino Acidsmentioning
confidence: 99%
“…Deletion of this plasmid revealed its high energetic burden (∼50% of dissimilatory expenditure) and resulted in global responses revealing the functional interconnectivity of the replicons [Trautwein et al, 2016;Wünsch et al, 2020]. (iv) The metabolism of P. inhibens DSM 17395 was studied in our laboratory on the physiological/proteogenomic level with respect to differential substrate utilization from complex substrate mixtures [Zech et al, 2013], degradation networks, growth energetics, and metabolic efficiency for amino acids and carbohydrates [Drüppel et al, 2014;Wiegmann et al, 2014;Wünsch et al, 2019], as well as the stoichiometric constraints with respect to varying N/Pprovision [Trautwein et al, 2017] and a multifaceted strategy to secure external nitrogen [Trautwein et al, 2018].…”
Section: Introductionmentioning
confidence: 99%